The library of Albertas Goštautas and the Lithuanian chronicles - Gudmantas, Kęstutis (Knygotyra, 2003)
The article deals with Albertas Goštautas (t1539) book-lists from year 1510-1511. Goštautas, voivode of Vilnius and chancellor of the GDL in 1522-1539, was an initiator of the creation of the Lithuanian Chronicles. Author of the present paper treats the book-lists as primarly means to understand the "laboratory" of the creation of the Chronicles and as the additional tools to find out the sources of it. He examines the content of the lists and tries to bring light on some "dark" cases since the meaning of some records is uncertain or still misinterpreted. He comes to the conclusion that the books of Goštautas were used to compile these narratives (e.g. "World chronicle" and "Polish Alexandria"), but since we know the collection status only from year 1510-1511, there could be changes until the chronicles were created (most probably the 3rd decade of the 16th century), especialy because of the acquisition of the new books.